If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2 (x+3) = 2 (x-3)
We simplify the equation to the form, which is simple to understand
2(x+3)=2(x-3)
Reorder the terms in parentheses
+(+2x+6)=2*(x-3)
Remove unnecessary parentheses
+2x+6=+2+*(+x-3+)
Reorder the terms in parentheses
+2x+6=+(+2x-6)
Remove unnecessary parentheses
+2x+6=+2x-6
We move all terms containing x to the left and all other terms to the right.
+2x-2x=-6-6
We simplify left and right side of the equation.
0x=-12
0=-12
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 5+25=2+73 | | x-5.5x=397 | | (2x-9)=33 | | e*779942286= | | -5+3x=9 | | 3x^2+4x=15+y | | 3(x-4)+5=14 | | 4z+3(5-z)=-(z-1)+12 | | 5x-3x=10+3x-3x | | 4(z^2+z-2)=-2z^2-7z+2 | | 12345678*87654321=1 | | 14=-4x-6 | | 52-9x=2x+19 | | 4(z^2+11z-2)=-2z^2-7z+2 | | 9-45+8*4=778*x | | .33x+.67x=10 | | 100P=2400 | | 3=-6x-9 | | 3.5x-1.5x=18 | | .07x=1.4 | | 2w(-6-1)= | | 20x^2-27x=14 | | 2x+9=29-3x | | 58-7x=29x+18 | | t^2-t+1=0 | | 4x+5=6x-7 | | x^2-5xy+4y^2=0 | | 3x*(-5xy)=a | | 5x-4(x-7)=4+2x | | 99+m^2=0 | | 7x+8y-9z=6 | | 13x+13=62-4x |